فاعلية التعليم الموديولي في تعلم بعض المهارات الاساسية على بساط الحركات الرياضية - عزال, ياسين حبيب; محسن, حسين علي (Sulaimani Journal for Humanities, 2018)
The research problem focused on how to prepare an educational program in which the work is based on the activity of the learner through passing through some of the different educational situations in which he acquires knowledge and skills. He has an active, effective and responsible component of his learning and how he chooses alternatives and means to help him acquire new experiences prepared in the form of educational modules. The aim of the research was to prepare an educational program according to the educational modules in teaching some basic skills on the ground floor. The students of the first stage in the Faculty of Physical Education and Sports Sciences were selected as a research sample. An educational curriculum was prepared and presented to the experts in the field of teaching methods by 8 modules in the form of educational modules lasting 8 weeks with one teaching unit per week at a rate of 90 minutes. The researchers reached a number of conclusions were: 1 - The educational modules give educational more freedom to choose the type of learning that corresponds to the capabilities of the potential learner 2 - The use of educational modules gives a clear diversity during the educational unit because of the variety of methods and applications 3 - Give greater opportunity to participate by students in the management of learning during the educational unit. 4- Educational modules work to invest time and effort for both teacher and student.